Artificial intelligence tools and higher education student’s engagement - Ezeoguine, Ebere Pearl; Eteng-Uket, Stella (Edukasiana: Jurnal Inovasi Pendidikan, 2024)
In the rapidly evolving landscape of higher education, the integration of Artificial Intelligence (AI) tools represents a pivotal paradigm shift, poised to redefine the very fabric of student engagement. Thus, as this integration becomes increasingly prevalent, it raises questions about its impact on student engagement. This prompted this study that sought to investigate AI tools' influence on student engagement in higher education. The study employed the descriptive survey design using a diverse sample of students from the University of Port Harcourt. A scale with validities and a high-reliability coefficient was used in obtaining data. Data were analyzed using mean, one-way, and two-way ANOVA. The result showed that the majority of the students were extremely engaged as a result of the influence of the use of AI tools, a significant difference existed in the engagement levels of students influenced by AI tools, and that neither gender nor age significantly affects engagement, suggesting a universal appeal of AI tools across demographics. The findings underscore the importance of inclusive AI integration in higher education, ensuring equitable and engaging learning experiences for students. These insights contribute to the ongoing discourse on leveraging AI tools to enhance student engagement in higher education settings